A tetramerization domain in prokaryotic and eukaryotic transcription regulators homologous to p53. Issue 3 (6th March 2023) - Bernardo, Nerea; Crespo, Isidro; Cuppari, Anna; Meijer, Wilfried J. J.; Boer, D. Roeland
Abstract : The tetramerization domain of the bacterial gene repressor Rco from Bacillus subtilis plasmid pLS20 was identified. The structure shows high similarity to the tetramerization domain of the p53 family of human tumor suppressors, despite having low sequence homology. Abstract : Transcriptional regulation usually requires the action of several proteins that either repress or activate a promotor of an open reading frame. These proteins can counteract each other, thus allowing tight regulation of the transcription of the corresponding genes, where tight repression is often linked to DNA looping or cross‐linking. Here, the tetramerization domain of the bacterial gene repressor Rco from Bacillus subtilis plasmid pLS20 (RcopLS20 ) has been identified and its structure is shown to share high similarity to the tetramerization domain of the well known p53 family of human tumor suppressors, despite lacking clear sequence homology. In RcopLS20, this tetramerization domain is responsible for inducing DNA looping, a process that involves multiple tetramers. In accordance, it is shown that RcopLS20 can form octamers. This domain was named TetDloop and its occurrence was identified in other Bacillus species. The TetDloop fold was also found in the structure of a transcriptional repressor from Salmonella phage SPC32H. It is proposed that the TetDloop fold has evolved through divergent evolution and that the TetDloop originates from a common ancestor predating the occurrence of multicellular life.